2014
DOI: 10.1039/c3dt53450b
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer stabilized Ln3+-doped CaMoO4 nanocrystals with high luminescence quantum efficiency and photocatalytic properties

Abstract: In this article, we discuss the microwave synthesis of sodium dodecyl sulphate (SDS) stabilized Ln(3+)-doped CaMoO4 nanocrystals (Ln(3+) = Eu(3+), Er(3+)/Yb(3+)). The nanocrystals are quite monodispersed with an average size close to 100 nm. FTIR and TGA analyses suggest strong binding of the SDS molecules to the CaMoO4 nanocrystals surface. The high dispersibility of the nanocrystals in water implies that SDS stabilizes the nanocrystals as a bilayer structure. The SDS coating also assists in the easy dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 107 publications
0
25
2
Order By: Relevance
“…Photoluminescence properties of CaMoO4:Eu 3+ have been extensively studied in bulk samples, 5,6,7,8 microparticles 3,9,10,11 and different types of nanoparticles. 12,13,14,15 However, very little attention has been paid to the substitution mechanism and crystal structure of Eu 3+ :CaMoO4 phosphors. In our recent paper on the photoluminescence of peanut-like CaMoO4:1%Eu 3+ architectures, we found that the unit cell parameters of the Eu 3+ -doped sample were slightly higher than those of the undoped material, in spite of the smaller ionic radius of Eu 3+ compared with Ca 2+ in eight-fold coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence properties of CaMoO4:Eu 3+ have been extensively studied in bulk samples, 5,6,7,8 microparticles 3,9,10,11 and different types of nanoparticles. 12,13,14,15 However, very little attention has been paid to the substitution mechanism and crystal structure of Eu 3+ :CaMoO4 phosphors. In our recent paper on the photoluminescence of peanut-like CaMoO4:1%Eu 3+ architectures, we found that the unit cell parameters of the Eu 3+ -doped sample were slightly higher than those of the undoped material, in spite of the smaller ionic radius of Eu 3+ compared with Ca 2+ in eight-fold coordination.…”
Section: Introductionmentioning
confidence: 99%
“…17 The potential applications of this kind of phosphors encompass biomedicine, 18 lighting, 10,13 and catalysis. 19 Up to now, several methods have been reported for the synthesis of CaMoO 4 microarchitectures with different shapes 20-27 . However, most of these methods conducted to particles with heterogeneous size and/or a certain degree of agglomeration, except in the case of the persimmon-like (2 µm) 20 particles obtained in a microwave reactor without temperature control and the spherical particles hydrothermally synthesized in the absence (5-6 µm) 22 or the presence (2 µm) 23 of a capping polymer (poly(diallyldimethyl-ammonium chloride).…”
Section: Introductionmentioning
confidence: 99%
“…This is also confirmed from the excitation spectrum which displays a broad absorption (shown in Figure S5). Moreover, the lifetime of this peak is around 30 μs which is much lower than that observed for the 4 f –4 f transition of Eu 3+ ions . However, we emphasize that the observed 30 μs lifetime for Eu 2+ is longer than observed in other matrices like Eu 2+ ‐doped GaN/SiO 2 nanocomposites, Eu 2+ ‐doped Ba 2 Si 5 N 8 , Eu 2+ ‐doped Na 2‐x Al 2‐x Si x O 4 (x=0.55), etc ,.…”
Section: Resultsmentioning
confidence: 56%